Korelasi Berat Badan dan Umur Sapi terhadap Berat, Volume Cairan dan Konsentrasi Prostaglandin F2α pada Vesikula Seminalis - Naela Wanda Yusria Dalimunthe; Agung Budiyanto; Erna Prawita Setyowati; Agustina Dwi Wijayanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Seminal vesicles were collected from 60 heads of Bulls which butchered in slaughter house (RPH) Yogyakarta. The aims of this study are knowing the relationship between body weight, age, fluids volume and concentration of prostaglandin F2 α (PGF2α) in seminal vesicle of beef cattle. Those seminal vesicles were gathered from bulls which recorded its body weight and age then measured its seminal vesicles for weight, fluids volume and PGF2α levels. The PGF2α level was measured by Enzyme-Linked Immunosorbent Assay. Statistical analysis was performed using one way – analysis of varian, regression and correlation with P<0.05. Body weight of bulls showed positive correlation with the weight of seminal vesicle and its fluids volume. However, PGF2α levels were not correlated with the body weight of cattle. Weight of seminal vesicles also exhibited positive correlation with volume of vesicle fluids but no correlation with PGF2α levels. Based on the age of bulls, there were no correlation withthe weight of seminal vesicles, seminal fluids volume and PGF2α levels. Those result indicated that the weight and fluids volume were affected by the body weight of bulls altough the PGF2α levels have a standard of developmentwhich seems affected by other factors such as concentration of androgen hormone.